The Relationship Between Emotion Regulation and Academic Stress in Madrasah Aliyah Students in Sidoarjo: Hubungan Antara Regulasi Emosi dengan Stres Akademik pada Siswa Madrasah Aliyah di Sidoarjo - Dzulfikri, Muhammad Ilham; Affandi, Ghozali Rusyid (Psikologia : Jurnal Psikologi, 2023)
This research is motivated by the phenomenon of stress academic experience experienced by students of Madrasah Aliyah Negeri (MAN) Sidoarjo. This study aims to determine the relationship between emotion regulation and academic stress achievement of the students of Madrasah Aliyah Negeri (MAN) Sidoarjo. This research belongs to the type of quantitative research with a correlational approach. This research was conducted at Madrasah Aliyah Negeri (MAN) Sidoarjo, East Java. The population in this study amounted to 1368 students, so from the calculation using the Slovin formula the sample used was 309 students who were taken using stratified random sampling technique. Data collection in this study used two psychological scales, namely the emotional regulation scale from the aspect of emotion regulation and obtained a reliability coefficient value of (α) 0.868 [1]. Scale academic stress from the aspect of academic stress and obtained a reliability coefficient value of (α) 0.920 [2]. Analysis of the data in this study using Pearson's Correlations and the analysis process using the JASP program version 0.13.1.0 for windows. The results showed that the value of r = -0.506 and p value = 0.001 where 0.001 <0.05, which means that there is a significant negative relationship between emotional regulation variables and academic stress in Madrasah Aliyah Negeri (MAN) Sidoarjo students. It is known that the value of r = -0.506, which means that the magnitude of the effect of emotional regulation on academic stress is quite large with a value of r = -0.506.